Pelatihan Olahan Minuman Jeruk Siam Di Desa Mensere Kecamatan Tebas Kabupaten Sambas - Kristiandi, Kiki; Kamila, Kamila; Sigiro, Oktavia Nurmawaty; Sangkala, Sangkala; Masara’T, Sudirman; Agam, Beryaldi (Pakis Journal Institute, 2025)
Siamese oranges are part of the abundant agricultural products in Sambas Regency. Siamese orange farming is able to become the main supplier for West Kalimantan, but during post-harvest the condition of Siamese oranges is uncontrolled, causing an unstoppable abundance in the market and causing a decrease in the price of Siamese oranges. The purpose of this community service is to provide training in processing Siamese oranges in Mensere Village, Sambas Regency. The approach method used is the provision of materials, modules, direct technical processing and discussion sessions. The results obtained from the activity were that the participants were happy with this training, besides that each participant could enjoy the processing process that had been practiced directly during the training and commented positively on the training that had been given. Training in processing drinks with Siamese oranges as raw materials is expected to foster skills and foster an entrepreneurial spirit in processing Siamese oranges. Another impact is to provide reinforcement of information on the condition of Siamese oranges, in addition to helping to increase creativity in overcoming the growth rate of Siamese oranges which during post-harvest cannot be stopped by the market.